Development of Islamic Teachings through the Translation of the Quran in Various National Languages - Moh. Ali Abdul Shomad Very Eko Atmojo; Elfi Mu'awanah; Ali Rohmad; Munardji Munardji; Umy Zahrok; Hibbi Farihin; Germino Wahyu Broto; Rifa Hidayah (Randwick International of Social Science Journal, 2022)
From the research on the translation of the Quran, in various countries in the center of places of worship, it is known that there are already translations so that it is hoped that it will increase interest in reading and understanding the contents of the Quran. The translation of the Quran is an interpretation of the holy book of Islam in a language other than Arabic. The Quran has been translated into most languages by the translator. The translation of the Quran has always been a troubled and difficult issue in Islamic theology. Because Muslims respect the Quran as a miracle and incomparable (i'jaz al-Quran), they argue that the Quranic text cannot be reproduced in other languages or other forms. The translation of the Quran in its history undergoes a lengthy process, for example from the question of authority or the legitimacy of the translator, the law of translation, coupled with the presence of the translation made by the Orientalists making many differences among the scholars in addressing the translation of the Quran.